Towards a psychobiotic therapy for depression: Bifidobacterium breve CCFM1025 reverses chronic stress-induced depressive symptoms and gut microbial abnormalities in mice - Tian, P. (Elsevier Inc, 2021)
10.1016/j.ynstr.2020.100216